METODE-METODE PEMBELAJARAN YANG DITERAPKAN DALAM PROSES PEMBELAJARAN DI INDONESIA - Nasron HK; Yola Novriyana; M. Agus Ainur Rosyid; Eva Susanti (STKIP Subang, 2024)
This research aims to analyze learning Learning Methodology is a science that discusses the methods used to carry out a process of interaction between students and teachers so that the goals that have been determined in education can be achieved. By guiding, training, giving examples, as well as organizing and facilitating various things for students to get used to learning. Various learning methods include discussion methods, demonstrations, lectures, experiments, sociodrama, recitation, problem solving, skills training, question and answer and apart from the methods mentioned there are many more various learning methods. Several of these methods can be varied or combined in carrying out teaching practice